Perceived load, fatigue and recovery responses during congested and non-congested micro-cycles in international football tournaments. Issue 12 (December 2021) - Noor, Denny; McCall, Alan; Jones, Mark; Duncan, Craig; Ehrmann, Fabian; Meyer, Tim; Duffield, Rob
Abstract: Objectives: To describe the perceived load, fatigue and recovery profiles during congested and non-congested schedules in international football tournaments. Design: Retrospective single-cohort observational study. Methods: Internal load (session-rating of perceived exertion [s-RPE]) and perceived ratings of fatigue, muscle soreness, psychological status, sleep quality, and sleep duration were recorded daily from 37 national team footballers during the competition phase of 3 international tournaments. ANOVA and Effect Size (ES) analyses compared individualised internal load and perceived response profiles between congested and non-congested acute 2-match schedules. Conditions included Acute Congestion (≤4 days between two matches), Non-Congestion (>4 days between two matches), Single-Match, and No-Match. Results: Significantly higher s-RPE match loads ( p < 0.001) within the single- and multi-match conditions resulted in significantly worsened ( p < 0.05) subjective ratings of perceived fatigue, muscle soreness and sleep duration in the 24–48 h post-match. Internal load profiles were not different between the Acute-Congestion or Non-congestion conditions ( p > 0.05); though Acute-Congestion had significantly worsened pre-match subjective ratings compared to Non-Congestion on both MD1 ( p = 0.040; ES = 0.94) and MD2 ( p = 0.033; ES = 0.94). However, between-match differences in Acute-Congestion showed no further impairments in perceived response between the first and second matches ( p > 0.05). Conclusions: During international tournaments, internal load and perceived fatigue/recovery profiles are largely determined by their exposure (or lack thereof) to match-play. Periods of acute match congestion impaired players pre-match perceived status when compared to non-congested microcycles. However, acute match congestion does not appear to exacerbate players post-match fatigue/recovery response within the context of international football tournaments.